Perceptions of cross-racial adoption in South Africa. - Hall, Victoria Ann (My University, 2010)
This study aimed to explore possible ways in which racist ideology and counter positions to this ideology are played out in discourses about cross-racial adoption (CRA) in the current post-apartheid context of South Africa. Three focus group interviews were conducted with 18 psychology students at the University of the Witwatersrand. The study adopted a social constructionist approach to knowledge and transcripts from the focus groups were analyzed using discourse analysis that combined techniques from Braun and Clarke (2006) and Parker (1992, 1999). Analysis revealed that students’ discussion focused mainly on the extent to which they thought black children raised by white parents should (or should not) be exposed to black culture. The discourses underlying these opinions appeared to gain social legitimacy for their speakers through three overarching repertoires, all of which tended to be used to divert attention away from the political ramifications of arguments. Firstly, participants claimed that their arguments were made with “the best interests of the child” at heart. Secondly, participants constructed particular meanings of the relationship between ‘race’ and identity by framing these meanings as central to “knowing who you are”. Thirdly, participants distanced themselves from accountability for their opinions by framing them as reflections of “other South Africans’ attitudes” towards ‘race’ and CRA. Overall, the analysis revealed that processes of racialisation show strong persistence in both black and white people’s discourses about CRA, but tend to be overtly expressed as a value and tolerance of different cultures and ethnicities. However, counter voices to these discourses did emerge in prominent challenges to the idea that ‘race’, ethnicity and culture are intrinsic and immutable features of people. Less prominent were the occasional counter voices that suggested these constructs are nevertheless pertinent, because of the ways in which they may be used to either challenge ‘racially’-derived inequalities between groups, or to fuel the prominence of racist ideology in society.
Keywords: Cross-racial; Adoption; South Africa; Racism; Race; Ethnicity; Culture; Identity; Discources; Ideology